A novel platelet lysate hydrogel for endothelial cell and mesenchymal stem cell-directed neovascularization. (May 2016) - Robinson, Scott T.; Douglas, Alison M.; Chadid, Tatiana; Kuo, Katie; Rajabalan, Ajai; Li, Haiyan; Copland, Ian B.; Barker, Thomas H.; Galipeau, Jacques; Brewster, Luke P.
Graphical abstract: Abstract: Mesenchymal stem cells (MSC) hold promise in promoting vascular regeneration of ischemic tissue in conditions like critical limb ischemia of the leg. However, this approach has been limited in part by poor cell retention and survival after delivery. New biomaterials offer an opportunity to localize cells to the desired tissue after delivery, but also to improve cell survival after delivery. Here we characterize the mechanical and microstructural properties of a novel hydrogel composed of pooled human platelet lysate (PL) and test its ability to promote MSC angiogenic activity using clinically relevant in vitro and in vivo models. This PL hydrogel had comparable storage and loss modulus and behaved as a viscoelastic solid similar to fibrin hydrogels despite having 1/4–1/10th the fibrin content of standard fibrin gels. Additionally, PL hydrogels enabled sustained release of endogenous PDGF-BB for up to 20 days and were resistant to protease degradation. PL hydrogel stimulated pro-angiogenic activity by promoting human MSC growth and invasion in a 3D environment, and enhancing endothelial cell sprouting alone and in co-culture with MSCs. When delivered in vivo, the combination of PL and human MSCs improved local tissue perfusion after 8 days compared to controls when assessed with laser Doppler perfusion imaging in a murine model of hind limb ischemia. These results support the use of a PL hydrogel as a scaffold for MSC delivery to promote vascular regeneration. Statement of Significance: Innovative strategies for improved retention and viability of mesenchymal stem cells (MSCs) are needed for cellular therapies. Human platelet lysate is a potent serum supplement that improves the expansion of MSCs. Here we characterize our novel PL hydrogel's desirable structural and biologic properties for human MSCs and endothelial cells. PL hydrogel can localize cells for retention in the desired tissue, improves cell viability, and augments MSCs' angiogenic activity. As a result of these unique traits, PL hydrogel is ideally suited to serve as a cell delivery vehicle for MSCs injected into ischemic tissues to promote vascular regeneration, as demonstrated here in a murine model of hindlimb ischemia.